DAMPAK PANDEMI COVID-19 TERHADAP DUNIA PENDIDIKAN DI INDONESIA: HAMBATAN DAN GANGGUAN PROSES PEMBELAJARAN DARING - Naufal Hafidzh; Raden Salma Azizah Roshadi; Syifa Alim Ramadhan; Usef Ilham (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2022)
The Covid-19 pandemic has an impact on various fields including education. The learning process shifts from face-to-face learning to distance learning.This step is taken to minimize the spread of COVID-19 in Indonesia. The purpose of this study is of course to find out the obstacles and challenges faced by students and lecturers during online lectures during this pandemic. This study also aims to analyze the positive aspects during online learning. In perfecting the research results, there are two stages in data collection. The first stage was filling out a questionnaire by 60 student respondents from the Faculty of Social and Political Sciences, UIN Bandung. The second stage is an interview with the lecturer. The results of this study can be concluded that there are pros and cons of participating in online lectures. Furthermore, students experience several difficulties which can be classified into technical difficulties, adaptation difficulties. Although students experience various difficulties during online lectures, they also feel the positive impact, one of which is having more free time.